Between Divine Transcendence and Social Praxis: Theoanthropology as a Solution to Contemporary Islamic Social Crises - Nasihun Amin; Moh. Nor Ichwan; David Ming (Assyfa Journal of Islamic Studies, 2025)
Amidst the complexities of the era of information disruption and the escalating global humanitarian crisis, mastering critical thinking skills based on social empathy and transformative religious literacy has become a fundamental urgency for students. Emancipatory and dialogical theological teaching has been identified as an effective and creative pedagogical strategy in revitalizing students' awareness to respond to structural injustice. This research is grounded in concerns about the paradox of religion in the Muslim world, where sacred values ​​are often reduced to legitimize patriarchal and authoritarian practices. In contrast to conventional theological studies, which tend to be trapped in normative-dogmatic rigidity, this article evaluates the significance of a paradigm shift toward theoanthropology in stimulating students' cognitive-analytical and psychomotor aspects in social action. The main objective of this study is to formulate an epistemological framework for Asghar Ali Engineer's theoanthropology as a solution to contemporary social crises. Using interpretive qualitative methods with a critical hermeneutics approach, this study analyzes Engineer's discourse, supported by a comprehensive secondary literature review. The results confirm that the theoanthropological paradigm successfully reconstructs the meaning of faith as an ethical praxis that aligns divine transcendence with the mandate of humanity. The findings indicate that critical awareness in textual interpretation is a key determinant of the success of this transformation, while rigid dogmatism has been shown to contribute little to social change. In conclusion, theoanthropology is seen as an urgent integrative framework to be adopted in Islamic education curricula to strengthen advocacy for human rights, gender justice, and harmony within pluralism.